Synthesis and Modification of Catalysts for the Partial Oxidation of n-Alkanes - N. Golub; V. Gomonaj; P. Gomonaj; K. Szekeresh (Adsorption Science & Technology)
The physical, chemical and catalytic properties of simple oxides and aluminosilicates of different composition, together with modifications of the same obtained by treatment with various reagents, have been studied experimentally. It has been shown that the use of simple oxides as catalysts led to the extensive oxidation of ethane while the use of aluminosilicates allowed the generation of formaldehyde, acetaldehyde and alcohols such as methanol and ethanol. The presence of phosphorus in the modified catalysts favoured the formation of aldehydes and led to an increase in aldehyde concentration as well as the appearance of alcohols among the oxidation products of n-alkanes, e.g. ethane. Thus, the addition of phosphoric acid to γ-Al 2 O 3 resulted in the formation of formaldehyde as a useful product.